2013
DOI: 10.17221/447/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Composition and sensory analysis for quality evaluation of a typical Italian cheese: influence of ripening period

Abstract: Papetti P., Carelli A. (2013): Composition and sensory analysis for quality evaluation of a typical Italian cheese: influence of ripening period. Czech J. Food Sci., 31: 438-444.Caciottina massaggiata di Amaseno, a typical dairy product of the Lazio Region prepared from buffalo milk, was analysed for moisture, fat, protein, pH, and acidity content at different storage (0, 3, 6, and 9 months after production). Cheeses were also evaluated for various sensory attributes (taste, flavour, texture, and overall accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
5
8
0
Order By: Relevance
“…This is similar to the findings of Papetti and Carelli (2013) who worked on composition and sensory analysis for quality evaluation of a typical Italian cheese and revealed that cheese were evaluated for various sensory attributes (taste, flavour, texture, and overall acceptability) during storage. In the affective tests, the panellists evaluated the samples for overall quality.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to the findings of Papetti and Carelli (2013) who worked on composition and sensory analysis for quality evaluation of a typical Italian cheese and revealed that cheese were evaluated for various sensory attributes (taste, flavour, texture, and overall acceptability) during storage. In the affective tests, the panellists evaluated the samples for overall quality.…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with Papetti and Carelli (2013), ripening determined a gradual increment of the attribute "yellow" from 30 to 60 and 90 d (P < 0.05). Although only partially sustained by our instrumental findings, this result is supported by other studies showing that the b* index (yellowness) increases during cheese ripening (El-Nimr et al, 2010;Jung et al, 2013;Nedomová et al, 2017).…”
Section: Sensory Profile and Consumer Likingsupporting
confidence: 73%
“…A sensory analysis by an expert panel may be very useful for identifying sensory attributes characterizing the cheese made with jenny milk. By using descriptive profiling techniques, such as quantitative flavor profiling (Stampanoni, 1993), the Spectrum method (Meilgaard et al, 2006), and quantitative descriptive analysis (QDA; Stone et al, 2004), several specific sensory profile have been developed for different types of cheeses, such as Scamorza (Braghieri et al, 2015), Caciottina (Papetti and Carelli, 2013), Cheddar (Young et al, 2004), Swiss cheese (Liggett et al, 2008), and so on.…”
Section: Short Communicationmentioning
confidence: 99%